Pengembangan Produk Multi-Item untuk Model Inventaris EOQ dengan Kualitas Barang Tidak Sempurna - Harahap, Fariz; Harkinata, Dwitra; Kamaralo, Melviani Karolin; Hidayat, Yosi Agustina (Journal of Research in Industrial Engineering and Management, 2025)
The competitive business environment encourages manufacturing companies to produce high-quality goods. However, companies often receive raw materials that do not meet production standards. These imperfect raw materials are caused by various factors such as improper shipping processes, damage, human error, and soon. This leads to a shortage of raw materials during the production process, necessitating reordering to meet production needs. The objective of this research is to develop a formulation model to determine the optimal ordering time intervals, order lot sizes, and total profit when a company has more than one raw material from a single supplier while considering the presence of defective goods. The research processes data by deriving the EOQ formula from a previous study model on single-item inventory policy with defective products, extending it to a multi-item inventory policy with defective products. The results show that the multi-item model generates 1.5 times higher total profit compared to the single-item model ($51,307 vs. $34,064 per unit per year). In addition, the ordering interval for the multi-item model is 52.1 days longer compared to the single-item model, which only has a 10-day interval. Finally, the multi-item model involves larger order lot sizes. Ordering raw materials simultaneously reduces ordering and holding costs, making the multi-item model more efficient and yielding higher profits than the single-item model.